Biết x \(\in\) N và x>2.tìm x sao cho: x(x-1)x(x-1)=(x-2)xx(x-1)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
X. ( X - 1) . X ( X - 1 ) = ( X - 2) XX ( X - 1)
X . X - X . 1 . X . X - X . 1 = X . X - X . 2 . X . X - X . 1
2X - X . 1 . 2X - X . 1 = 2X - X. 2 . 2X - X
2 . 1 . 2 . 1 = 2 . 2 . 1
4 = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x.\left(x-1\right).x.\left(x-1\right)=\left(x-2\right).x.x.\left(x-1\right)\left(x\in N;x>2\right)\)
\(\Rightarrow\left(x^2-x\right).\left(x^2-x\right)=\left(x-2\right).x^2.\left(x-1\right)\)
\(\Rightarrow x^4-x^3-x^3+x^2=\left(x-2\right).\left(x-1\right).x^2\)
\(\Rightarrow x^4-2x^3+x^2=\left(x^2-x-2x+2\right).x^2\)
\(\Rightarrow x^4-2x^3+x^2=x^4-x^3-2x^3+2x^2\)
\(\Rightarrow x^4-2x^3+x^2-x^4+x^3+2x^3+2x^2=0\)
\(\Rightarrow x^4-x^4+2x^3-2x^3+2x^2+x^2+x^3=0\)
\(\Rightarrow x^2.\left(2+1+x\right)=0\)
\(\Rightarrow x^2=0hoac2+1+x=0\)
\(\Rightarrow x^2=0^2\) \(\Rightarrow3+x=0\)
\(\Rightarrow x=0;\Rightarrow x=-3\)
Mà \(x\in N;x>2\)
\(\Rightarrow x\in\varnothing\)
Vậy \(x\in\varnothing\)
Chúc bn học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
1/x +1/y=2/3 <=> 3(x+y)=2xy; mà x+y=6
=> 3.6=2xy => xy=9
<=> x(6-x)=9 <=> x2-6x+9=0
<=> (x-3)2=0 => x=3
y=6-3=3
Ds: x=y=3